Majorana CP violating phases - Chao-Shang Huang (Nuclear Physics B)
The two Majorana CP-violating phases can not be determined by experiments on neutrino oscillations. It is difficult even almost impossible to measure two Majorana CP-violating phases since they are only sensitive to lepton-number-violating processes. One must take some assumption on the structure of neutrino mass matrix and their flavor mixing mechanism hidden behind in phenomenological models in order to determine Majorana CP-violating phases. Two models on the symmetry of the neutrino mass matrix are proposed in this paper. The Majorana CP-violating phases and the effective Majorana neutrino mass mee are computed in the two models. Using data in experiments on neutrino oscillations and using the limit of the absolute neutrino mass scale which is from cosmological observations, the numerical values of the Majorana CP-violating phases and the effective Majorana neutrino mass mee are obtained.